PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Yuliani, Indah; Katim, Katim (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
This study aims to analyze the effect of job satisfaction and commitment to OCB.Data used in this study is the primary data obtained from the questionnaire. The number of samples as many as 62 respondents who are the entire population of PT. TAW area west Jakarta. The analysis technique used is multiple regression methods. The results showed that Organizational Commitment has a significant positive effect on OCB. Job satisfaction has a significant positive effect on OCB and Organizational Commitment and Job Satisfaction has a significant positive effect on OCB. Suggestion in this research job satisfaction most dominantly influence to OCB on salary indicator, promotion in this case company expected to increase employee job satisfaction by increasing employee salary, clarify system of appointment of permanent employees and career ladder, expected to increase organizational commitment to every employee for example with reward employees with integrity and high dedication to the company. Keywords: job satisfaction, commitment, OCB